Ecoinovações em energias renováveis no Parque Tecnológico Itaipu: abordagem da transição sociotécnica - Carvalho, Andriele de Prá (2016)
Environmental problems arising from uncontrolled growth increased interest in studies that combine innovation and sustainability. Innovative technological trajectories began to seek efficient ways of environmental preservation, combined with organizational competitive advantages. Thus, ecoinnovation is an approach that helps to understand the relation among society, economy and environment. Technological parks are considered innovative environments for the development of new technologies, a dynamic that can be explained by the theory of socio-technical transition. The thesis to be proven in this research is that technology parks are supportive environments for development and diffusion of eco-innovation and its dynamic process and depend on the way actors interact at different levels of socio-technical system. The overall aim of the thesis was to analyze how to develop the eco-innovations in renewable energy at the Itaipu Technological Park from the socio-technical transition approach (multi-level, multi-phase and multi-actors). Theoretically this thesis helps to explain the development and diffusion of technologies in sustainable energy technology parks from eco-innovation, evolutionary theory and the theory of socio-technical transition approaches, an unprecedented contribution in the Brazilian academic space. The four cases analyzed in this thesis, were made by companies and eco-innovative projects in the Renewable Energy area of Itaipu Technological Park, as follows: Ap Energia, Esco Iguassu, Cibiogás and Hydrogen Project. The methodology was based on multiple case study of qualitative nature that used ethnographic resources and sensitizers concepts from the Practice Theory to collect the data, which were supported by content analysis with the help of Atlas IT software and the triangulation of information. The main results showed that the ITP with the support of his sponsor Itaipu Binacional created a conducive environment for the development of eco-innovative companies in renewable energy, encouraging the exchange of knowledge among the cluster companies, promoting partnerships with national and international companies for the technology development, enabling partnerships with local universities, touting access to national organizations and institutions to change the current rule especially regarding laws and policies, opening paths to facilitate the financing of technological development. The physical infrastructure, their laboratories, their eco-innovative culture, their actions for the development of renewable energy cluster prove the thesis that the ITP is characterized as an environment that creates windows of opportunities for the development of eco-innovations, playing a key role in scientific and technological development of these projects and companies, opened windows of opportunities, partnerships and financing, but must move on to the process of diffusion of these technologies in the market. In this sense, the park, through the support of Itaipu Binacional can advance and expand its operations by opening new ways to strengthen these companies in terms of business management, financial management and market, aiming to disseminate these technologies and the competitiveness of enterprises, strengthening their social and economic role in the socio-technical transition to sustainability.